Robot Navigation control through EEG Based Signals (International Journal of Engineering and Computer Science, 2014)
The Electroencephalogram (EEG) is a biological signal that represents the electrical activity of the brain. Brain potentials have been of scientific interest since the discovery of the Electroencephalogram (EEG). This project develops a brain-computer-interface (BCI) based manmade robot control system with help of MATLAB and FPGA KIT. The system consists of an electroencephalograph (EEG) database and a manmade robot. The control loop includes a brain signals stored database, a robot interface and fpga board. The goal of our study is to control navigation of robot through neural signals acquired by EEG database. When the database having signals of “turn right”,  “turn left” , “move forward” , “turn 45 degree” , “pick up and pick down” Then the developed control system is a powerful tool to examine relationships between complex manmade robot behaviours and given database signals. Mapping brain activity patterns in external actions has been studied in recent decades and is the base of a brain-computer interface. This type of interface is extremely useful for people with ill health, where one can control robotic systems that support, or even replace, non-functional body members. Part of the studies in this area focuses on non-invasive interfaces, in order to increase the interface usage to a larger number of users without surgical risks. Our results demonstrate that an EEG- data based brain–computer interface can be used for refined robotic interaction with the environment, involving not only navigation But also perform some task.